THE EFFECTIVENESS OF PEPPER LEAVES (Piper nigrum L.) AS A LARVACIDE OF Aedes aegypti MOSQUITO - Yuyun Solihat; Emantis Rosa; Gina Dania Pratami; Nuning Nurcahyani (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2021)
Dengue Hemorrhagic Fever (DHF) cases are quite high in Indonesia. One of the causes of high dengue cases is the high vector population, namely the Aedes aegypti mosquito. Mosquito control Ae. aegypti one of them uses larvicides to break the chain of reproduction. The use of chemical-based larvicides can be bad because it can pollute the environment and cause resistance. As an alternative, you can use natural larvicides made from plants. One of the plants that have the potential as larvicides are pepper (Piper nigrum L.) because it contains compounds that can be toxic to insects such as saponins, flavonoids, alkaloids, and essential oils. In addition, pepper plants are widely cultivated in Lampung and are easy to obtain. The purpose of this study was to determine the effectiveness of pepper leaf (P. nigrum L.) as larvicide for Ae. aegypti. This study used a completely randomized design (CRD). There was 1 control and 5 treatments in the form of pepper leaf extract with concentrations of 0.2%, 0.4%, 0.6%, 0.8%, and 1%. The test material used was Ae. aegypti instar III. Each treatment used 25 larvae with 4 repetitions. Observations were made after 24 hours of treatment. The data obtained in the form of the number of larval deaths were analyzed using one-way ANOVA and Post hoc LSD test. The results of this study showed a significant difference (p = 0.000), and it was found that a concentration of 1% was the most effective concentration as a larvicide for Ae. aegypti with a larval mortality percentage of 92%.